Influence of school culture and climate in Tamil schools, Malaysia - Koundyannan, Thiruchelvan (Human Resource Management Academic Research Society, 2020)
School culture and climate are two uncertain aspects of the management and administration of schools in a VUCA world. This study was conducted to examine the influence of factors in the school culture and climate for the school effectiveness of Sekolah Jenis Kebangsaan Tamil (SJKT) in Malaysia. This research involved a total of 312 teachers from 82 SJKT schools in Peninsular Malaysia. Data were collected by strata using the School Culture Survey (Gruenert, 1998), School Climate Instrument (Ross & Lowther, 2003) and School Effectiveness Instrument (Lezotte dan Snyder, 2011). The results of the stepwise multiple regression analysis show that the School Culture Regression Model P5 (unity of purpose, collaborative leadership, learning partnership, professional development, and teacher’s collaboration) contributed for 65.0% (R^2=.644) changes in variance in school effectiveness [F(5,306)=113.609, p<0.5]. The school climate regression model P4 (leadership, environment, instruction, and collaborations) contributed 67.8% (R^2=.673) of the variance in school effectiveness [F(4,307)=161.265, p<0.5]. The combination of school culture (?=.542, p<0.5) and school climate (?=.317, p<0.5) significantly contributed 66.8% (R^2=.666) of the variance change [F(2,309)=310.731, p<0.5]. The results of the stepwise multiple regression analysis showed that school Culture influence (?=.542, p<.05) higher than school climate (?=.317, p<.05). This model contributes to predicting the impact of school culture and climate on school effectiveness.